ZMFLS1 PROMOTES OXIDATIVE STRESS RESISTANCE BY REGULATING FLAVONOL BIOSYNTHESIS IN TRANSGENIC ARABIDOPSIS THALIANA - Y. Fan1; H. Li2; R. Fan; H. Zhang; X. Zhao; B. Li1 (Journal of Animal and Plant Sciences, 2021)
Many biological and abiotic stresses can lead to excessive reactive oxygen species accumulation and oxidative damage in plants. The purpose of the present study was to elucidate the function of maize flavonol synthase 1 (ZmFLS1) in alleviating oxidative stress. The coding sequence of ZmFLS1 was cloned from maize B73 complementary DNA and was introduced into Arabidopsis thaliana. Two ZmFLS1 overexpression lines, OE-6 and OE-8, showed a significant increase in the accumulation of flavonoids, especially flavonols. The antioxidant capacity test showed that overexpression of ZmFLS1 resulted in a higher oxygen radical scavenging rate. Consistent with those, transgenic plants with ZmFLS1 overexpression showed enhanced oxidative stress tolerance and lower oxidative damage. In conclusion, ZmFLS1 promoted plant oxidative stress tolerance through regulating flavonoid biosynthesis and accumulation, especially flavonols, and ZmFLS1 has the potential in mitigating oxidative damage caused by environmental stress in plants.
Keywords: ZmFLS1; Flavonols; Oxidative stress; MDA (Malondialdehyde)